Educational Values in Finding Dory Movie Script and Teaching Speaking Application - Nugraeni, Ismawati Ike; Rokhayati, Titi; Dewi, Liska Erliana Puspita (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aimed to analyze types of educational value found in Finding Dory movie script and its application in teaching speaking for vocational high school students. This research was a qualitative research. The instrument of the research was the researchers. The object of the research was movie entitled Finding Dory. The data were taken from the dialogues performed by the characters in the movie. In analyzing data, the researchers took some steps such as: watching the movie and downloading the movie script, taking the utterances, and transcribing the data. There were some procedures in analyzing the data. They were describing the data into dialogue form, describing the context, and analyzing the types of educational value. The result of this research showed that Finding Dory movie script contained 175 data of educational value. There were: honesty 7.43%, brave 5.14%, peace 4%, confidence and potential 26.29%, self-discipline and moderation 11.43%, purity 2.29%, loyalty and trustworthiness 5.71%, respect 12%, love and affection 6.85%, unselfish 6.29%, kind and friendly 12%, and fair and humanist 0.57%. Confidence and potential were the most dominant types of educational value that often found in Finding Dory movie script. Educational value found in Finding Dory movie script could be applied in teaching speaking in asking and giving opinion at the eleventh grade of student of vocational high school. Keywords: Educational Value, Movie Script, Teaching Speaking.